2020
DOI: 10.7717/peerj.9939
|View full text |Cite
|
Sign up to set email alerts
|

An empirical examination of sample size effects on population demographic estimates in birds using single nucleotide polymorphism (SNP) data

Abstract: Sample size is a critical aspect of study design in population genomics research, yet few empirical studies have examined the impacts of small sample sizes. We used datasets from eight diverging bird lineages to make pairwise comparisons at different levels of taxonomic divergence (populations, subspecies, and species). Our data are from loci linked to ultraconserved elements and our analyses used one single nucleotide polymorphism per locus. All individuals were genotyped at all loci, effectively doubling sam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…A second potential caveat to our study may be the rather limited population sizes (n≥3). While performing a population genetic study with populations represented by only three specimens was previously and usually considered too small, recent studies have shown that accurate population parameters such as F st-values or genetic diversity measurements can be obtained when a large number of SNPs are used to compensate for such low population sizes ( Nazareno et al, 2017 ; McLaughlin and Winker, 2020 ). Here, by conducting a genomic study with approximately 14,000 SNPs per species after filtering, we met the latter criteria.…”
Section: Discussionmentioning
confidence: 99%
“…A second potential caveat to our study may be the rather limited population sizes (n≥3). While performing a population genetic study with populations represented by only three specimens was previously and usually considered too small, recent studies have shown that accurate population parameters such as F st-values or genetic diversity measurements can be obtained when a large number of SNPs are used to compensate for such low population sizes ( Nazareno et al, 2017 ; McLaughlin and Winker, 2020 ). Here, by conducting a genomic study with approximately 14,000 SNPs per species after filtering, we met the latter criteria.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the potential effect of our sample sizes, we performed a rarefaction analysis, which showed that good estimates of H e and pairwise F ST can be obtained from subsample sizes as small as four diploid individuals (Figure S1 ), supporting the robustness of genetic diversity and differentiation estimates when a large number of SNPs are available (Nazareno et al., 2017 ). Although desirable, we were unable to perform robust estimations of past and contemporary effective population size, as both the sample size (between 14 and 16 gene copies) and the short time‐scale at which the demographic events occurred (~30 generations) limit the use of both linkage and coalescent approaches (McLaughlin & Winker, 2020 ; Nunziata & Weisrock, 2018 ; Robinson et al., 2014 ; van der Zee et al., 2022 ). Nevertheless, the frequency distribution of polymorphisms within a population still carries information about recent processes.…”
Section: Methodsmentioning
confidence: 99%
“…However, approaches are now available to test for introgression separate from incomplete lineage sorting, using both population and phylogenomic approaches (e.g., Pickrell and Pritchard 2012 ; Pease and Hahn 2015 ; Wen et al 2018 ). How taxa are sampled can also affect the ability to resolve recent population divergence with gene flow; sampling of multiple geographically dispersed individuals per taxon should result in improved parameter estimates compared with just one or two individuals ( Robinson et al 2014 ; McLaughlin and Winker 2020 ; e.g., Teng et al 2017 ; Linck et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%